Growth and Education - Aghion, Philippe (World Bank, Washington, DC, 2017)
Does education matter for growth? Which type of education investment (primary, secondary, or tertiary) matters most? Is there a relationship between growth or innovation and the governance of higher education? This paper surveys recent attempts at answering these questions. It first contrasts the 'Lucas approach,' whereby growth is affected by the accumulation of human capital, with the 'Nelson?Phelps approach,' whereby growth is affected by the stock of human capital and by its interaction with the underlying process of technological innovation. Then the paper argues that growth in countries that are close to the world technological frontier benefit more from tertiary education, whereas countries that lie below the frontier benefit more from primary and secondary education. Finally, the paper discusses the relationship between innovation and the governance of universities.